2003
DOI: 10.1179/joc.2003.15.6.579
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Risk Factors of 339 Cases of Infective Endocarditis: Report from a 10-year National Prospective Survey in the Slovak Republic

Abstract: The authors studied the etiology, outcome and risk factors of 339 cases of infective endocarditis (IE) in Slovakia over the last 10 years. Aortic valve was infected in 59.9%, mitral in 38.1% and tricuspidal/pulmonary in 5.0% of cases. The majority of IE were caused by staphylococci (29.2%), 15.0% were due to viridans streptococci, 7.4% due to Enterococcus faecalis, 3.9% due to the HACEK group (Haemophilus spp., Actinobacillus spp., Corynebacterium spp., Eikenella spp., Kingella spp.) and 39.2% were culture neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 12 publications
2
15
0
2
Order By: Relevance
“…In the majority of retrospective studies published during the 1990's, the oral cavity was identified to be the portal of entry of the causative microbial agent in 14-20% of cases of bacterial endocarditis (1)(2)(3), with the prevalence of bacterial endocarditis of possible oral origin in recently published series being similar to that reported in these older series (4)(5)(6).…”
Section: Introductionsupporting
confidence: 54%
“…In the majority of retrospective studies published during the 1990's, the oral cavity was identified to be the portal of entry of the causative microbial agent in 14-20% of cases of bacterial endocarditis (1)(2)(3), with the prevalence of bacterial endocarditis of possible oral origin in recently published series being similar to that reported in these older series (4)(5)(6).…”
Section: Introductionsupporting
confidence: 54%
“…Prevalence rates of IE with negative blood cultures reported in the literature range between 10 and 30% of IE cases [1][2][3][4][5][6][7], with even higher rates reported from some countries, for example Pakistan and Eastern Europe [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As to fungal endocarditis, we have not recorded patients in our center, and the related reports were only scatter cases. Reported prevalence rates of IE with negative blood cultures ranged between 10% and 30% and found even higher in Pakistan and Eastern Europe (16,17). One of the main causes of negative blood cultures in IE patients is antibiotic pretreatment.…”
Section: Discussionmentioning
confidence: 99%